ショワキチ ニ オケル 1969ネン ノ オゾン ゼンリョウ カンソク - 石田, 恭市; イシダ, キョウイチ; 鈴木, 剛彦; スズキ, タケヒコ; 酒井, 重典; サカイ, シゲノリ; ISHIDA, Kyoichi; SUZUKI, Takehiko; SAKAI, Shigenori (国立極地研究所, 1971)
P(論文) Total ozone observations with Dobson's ozone spectorophotometer were made at Syowa Station in 1969. The procedures is described, along with a newly tested focussed image method using moonlight during the dark season. The amount of total ozone is larger in summer and a noticeable change in the values of each 10-day means is observed at about the time of the stratowarming (from September to October). The increase in the mean monthly values is related to the increase in northerly wind component in the upper-air (at 500mb-100mb level), suggesting the meridional transport of ozone-rich air masses from lower latitudes. departmental bulletin paper